2019
DOI: 10.3390/s19224934
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Detecting Sleep Apnea Using Deep Learning

Abstract: Sleep apnea is a sleep related disorder that significantly affects the population. Polysomnography, the gold standard, is expensive, inaccessible, uncomfortable and an expert technician is needed to score. Numerous researchers have proposed and implemented automatic scoring processes to address these issues, based on fewer sensors and automatic classification algorithms. Deep learning is gaining higher interest due to database availability, newly developed techniques, the possibility of producing machine creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 80 publications
0
60
0
1
Order By: Relevance
“…A recent comprehensive survey showed that the vast majority of deep learning methods for sleep breathing disorders have been devoted to signals [ 46 ]. Few studies considered single channel respiration inputs for deep learning apnea detection models [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive survey showed that the vast majority of deep learning methods for sleep breathing disorders have been devoted to signals [ 46 ]. Few studies considered single channel respiration inputs for deep learning apnea detection models [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that investigated deep learning methods in sleep apnea show improvement over classical machine learning methods [ 46 ]. While the majority of studies considered signal [ 18 , 19 , 20 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], a very limited number of them investigated respiration signals.…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…On the other hand, a qualitative technique using a random forest classifier allowed to report 86% of accuracy (with the sensitivity of 96% and the specificity of 76%), when setting a binary border at the level of AHI=15. Interestingly, in the review on detecting sleep apnea using deep learning methods [37], only a single study focused on breathing sounds by Kim et al was found [38]. In that study, they used breathing sounds with the accuracy of 88.3% for four-group AHI classification, and 92.5% using binary classification.…”
Section: Discussionmentioning
confidence: 99%
“…Full reviews on commercial devices [11], algorithm performance [12], deep learning [13] and classification methods [14] for OSA detection have been performed. Different source signals, such as oximetry [15] [16], electrocardiogram (ECG) [17] [18], respiration [19] [20], and sound [21], have been previously evaluated.…”
Section: Introductionmentioning
confidence: 99%